Profitability, leverage, firm size, and tax avoidance model relationship: A case of the manufacturing sector - Amelia Oktrivina (Jurnal Riset Manajemen dan Bisnis, 2022)
Tax avoidance is one of the issues that has attracted researchers' interest in financial management, and efforts to understand the causative factors are of serious concern. This study explicitly reveals the determinants of tax avoidance using the fundamental factor approach (profitability, leverage, and firm) in the automotive sector manufacturing companies. Moreover, the role of size as a moderator is also tested in the proposed model. The data analysis technique shows that profitability, leverage, and size have a negative effect on tax avoidance. Furthermore, the confirmed size moderates the relationship between leverage and tax avoidance but not profitability. The results of this study provide new insights into the role of size, which has been proven as a moderator of tax avoidance.